Non-specific low back pain in male professional football players in the Turkish super league - Çali, A.; Gelecek, N.; Subasi, S.S. (Science & Sports, 2013)
Objectives: The aim of this study was to determine the prevalence and possible causes of non-specific low back pain (LBP) in male professional football players in the Turkish Super League. Methods: A total of 121 players were questioned for demographic variables and whether they have had LBP in the last year. Player position, training characteristics, number of years as a football player, injury background and last season statistics were investigated. Flexibility of low back and hamstring muscles, and hamstring muscle length were measured. Results: Thirty-eight football players reported non-specific LBP in last year with a prevalence of 31.4%. It was found that more matches played in a starting position and hamstring muscle shortness were significant factors for developing non-specific LBP (P < 0.05). Conclusion: The prevalence of non-specific LBP in Turkish male professional football players is 31.4%, similar to the literature findings. Hamstring muscle shortness and high numbers of matches played as a starter are important factors for non-specific LBP. These findings should be considered for injury prevention. Causes of LBP in football players require further investigation. Studies should be performed on a larger sample of participants to attain more certain results.